The impact of incentive mechanism and knowledge sharing motivation on the satisfaction of fanpage's members on Facebook in Vietnam. (5th March 2020) - Pham, Quoc Trung; Tran, Ngoc Kien Phuc
Social networking is more and more utilised by many companies in marketing, knowledge management, entertainment, and collaboration. However, how to take advantage of social medias to support marketing activities, attracting more customers and encouraging knowledge sharing is still a difficult question. In addition, the research on knowledge sharing through social networking sites in Vietnam is fairly limited. In this study, the relationship between incentive mechanism, knowledge sharing motivation and the satisfaction of fanpage members on Facebook will be evaluated. Data were collected through a survey in Vietnam. The research model is tested through quantitative analysis on SPSS/AMOS software. The results show that Knowledge sharing motivation and Incentive mechanism have positive impacts on the Satisfaction of fanpage members, while the Incentive mechanism also has a positive impact on Knowledge sharing motivation. Based on this result, suitable Incentive mechanism should be suggested for increasing both members' satisfaction and knowledge sharing motivation.